Perspectives: Effect of global change drivers on carbon fluxes and resilience of European forests - Mana Gharun; Charlotte Angove; Mirco Migliavacca; Yu Zhou; Kate Buckeridge; Cristina Branquinho; Alessio Collalti; Line Nybakken; Miglena Zhiyanski; Murat Sarginci; Ismail Koc; Abdullah Huseyin Donmez; et al. (Forest Ecology and Management, 2026)

Diversity, root tip vitality and soil-driven variations of Ectomycorrhizal communities in Pinus cembra forests from alpine treelines - Hangyu Lan; Markus Gorfer; Burenjargal Otgonsuren; Douglas L. Godbold (Plant and Soil, 2026)
Background and aims Swiss stone pine ( Pinus cembra ) is dominant tree species in the treeline ecotone of the European Alps. Ectomycorrhizal (EM) fungi are often used in treeline reestablishment with Pinus cembra , yet our understanding of natural EM communities is limited. Methods In three alpine regions of the Austrian Alps on both silicate and calcareous bedrocks we determined the EM communities on roots of Pinus cembra and related these to soil chemical properties. Results The taxa composition of the EM communities was similar for the different sites, but the structure in terms of abundance varied greatly. The community of the calcareous sites differed from the silicate sites, and correlated to the level of exchangeable Ca. Similarly, on the silicate sites the levels of total Al and Fe influenced the community structure. Conclusion The composition of EM fungal communities of Pinus cembra is strongly influenced by soil factors.

Ectomycorrhizal exploration types shape soil enzyme activity, decomposition, and nitrogen dynamics in subalpine forests - Lixia Wang; Haoying Gao; Shuangjia Fu; Huichao Li; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; et al. (Plant and Soil, 2026)

Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

Multiyear Drought Strengthens Positive and Negative Functional Diversity Effects on Tree Growth Response - Hernán Serrano‐León; Haben Blondeel; Paula Glenz; Johannes Steurer; Florian Schnabel; Lander Baeten; Joannès Guillemot; Nicolas Martin‐StPaul; Georgios Skiadaresis; Michael Scherer‐Lorenzen; Damien Bonal; Matthieu Boone; et al. (Global Change Biology, 2025)
Mixed‐species forests are proposed to enhance tree resistance and resilience to drought. However, growing evidence shows that tree species richness does not consistently improve tree growth responses to drought. The underlying mechanisms remain uncertain, especially under unprecedented multiyear droughts. We used a network of planted tree diversity experiments to investigate how neighborhood tree diversity and species' functional traits influence individual tree responses to drought. We analyzed tree cores (948 trees across 16 species) from nine young experiments across Europe featuring tree species richness gradients (1–6 species), which experienced recent severe droughts. Radial growth response to drought was quantified as tree‐ring biomass increment using X‐ray computed tomography. We applied hydraulic trait‐based growth models to analyze single‐year drought responses across all sites and site‐specific responses during consecutive drought years. Growth responses to a single‐year drought were partially explained by the focal species' hydraulic safety margin (representing species' drought tolerance) and drought intensity, but were independent of neighborhood species richness. The effects of neighborhood functional diversity on growth responses shifted from positive to negative with increasing drought duration during a single growing season. Tree diversity effects on growth responses strengthened during consecutive drought years and were site‐specific with contrasting directions (both positive and negative). This indicates opposing diversity effects pathways under consecutive drought events, possibly resulting from competitive release or greater water consumption in diverse mixtures. We conclude that tree diversity effects on growth under single‐year droughts may differ considerably from responses to consecutive drought years. Our study highlights the need to consider trait‐based approaches (specifically, hydraulic traits) and neighborhood scale processes to understand the multifaceted responses of tree mixtures under prolonged drought stress. This experimental approach provides a robust framework to test biodiversity‐ecosystem functioning (BEF) relationships relevant for young, planted forests under increased drought stress.

Forest temperature buffering in pure and mixed stands: A high-resolution temporal analysis with generalized additive models - Matthias Steinparzer; Loïc Gillerot; Boris Rewald; Douglas L. Godbold; Daniela Haluza; Qiwen Guo; Sonja Vospernik (Forest Ecology and Management, 2025)

Soil phosphorus dynamics and its correlation with ectomycorrhizal fungi following forest conversion in subtropical conifer (Picea asperata) forests - Lixia Wang; Shiyu Song; Huichao Li; Yang Liu; Lin Xu; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; Zhenfeng Xu; Li Zhang; et al. (European Journal of Soil Biology, 2025)

Variability in fine root decomposition after forest thinning: effects of harvest intensity and root size - Dong Wang; Mathias Neumann; Mathias Mayer; Douglas L. Godbold; Hangyu Lan; Xinli Chen; Qingwei Guan (European Journal of Forest Research, 2024)

Tree drought–mortality risk depends more on intrinsic species resistance than on stand species diversity - Renaud Decarsin; Joannès Guillemot; Guerric le Maire; Haben Blondeel; Céline Meredieu; Emma Achard; Damien Bonal; Hervé Cochard; Déborah Corso; Sylvain Delzon; Zoé Doucet; Arsène Druel; et al. (Global Change Biology, 2024)
Increasing tree diversity is considered a key management option to adapt forests to climate change. However, the effect of species diversity on a forest's ability to cope with extreme drought remains elusive. In this study, we assessed drought tolerance (xylem vulnerability to cavitation) and water stress (water potential), and combined them into a metric of drought–mortality risk (hydraulic safety margin) during extreme 2021 or 2022 summer droughts in five European tree diversity experiments encompassing different biomes. Overall, we found that drought–mortality risk was primarily driven by species identity (56.7% of the total variability), while tree diversity had a much lower effect (8% of the total variability). This result remained valid at the local scale (i.e within experiment) and across the studied European biomes. Tree diversity effect on drought–mortality risk was mediated by changes in water stress intensity, not by changes in xylem vulnerability to cavitation. Significant diversity effects were observed in all experiments, but those effects often varied from positive to negative across mixtures for a given species. Indeed, we found that the composition of the mixtures (i.e., the identities of the species mixed), but not the species richness of the mixture per se, is a driver of tree drought–mortality risk. This calls for a better understanding of the underlying mechanisms before tree diversity can be considered an operational adaption tool to extreme drought. Forest diversification should be considered jointly with management strategies focussed on favouring drought‐tolerant species.

Assessment of soil erosion in the Upper Citarum watershed for sustainability of the Saguling reservoir: unmixing model approach - Leons Rixson; Duan Wenbiao; Barokah Aliyanta; Douglas Godbold; Ali Arman Lubis; Eka Djatnika Nugraha (Environmental Monitoring and Assessment, 2024)

Forests are chill: The interplay between thermal comfort and mental wellbeing - Loïc Gillerot; Kevin Rozario; Pieter de Frenne; Rachel Oh; Quentin Ponette; Aletta Bonn; Winston Chow; Douglas Godbold; Matthias Steinparzer; Daniela Haluza; Dries Landuyt; Bart Muys; et al. (Landscape and Urban Planning, 2024)

Enhancing Tree Performance Through Species Mixing: Review of a Quarter-Century of TreeDivNet Experiments Reveals Research Gaps and Practical Insights - Leen Depauw; Emiel De Lombaerde; Els Dhiedt; Haben Blondeel; Luis Abdala-Roberts; Harald Auge; Nadia Barsoum; Jürgen Bauhus; Chengjin Chu; Abebe Damtew; Nico Eisenhauer; Marina V. Fagundes; et al. (Current Forestry Reports, 2024)

Particulate matter accumulation by tree foliage is driven by leaf habit types, urbanization- and pollution levels - Matthias Steinparzer; Johanna Schaubmayr; Douglas L. Godbold; Boris Rewald (Environmental Pollution, 2023)

Estimating the response of Himalayan old-growth mountain forests to decreased monsoon precipitation - Norbu Wangdi; Iftekhar Uddin Ahmed; Mathias Mayer; Mani Prasad Nirola; Karma Orong; Norbu Zangmo; Douglas L. Godbold; Georg Gratzer; Andreas Schindlbacher (Agricultural and Forest Meteorology, 2023)

Non-structural carbohydrate concentrations of Fagus sylvatica and Pinus sylvestris fine roots are linked to ectomycorrhizal enzymatic activity during spring reactivation - Christoph Rosinger; Hans Sandén; Douglas L. Godbold (Mycorrhiza, 2020)
We evaluated whether changes in fine root non-structural carbohydrate reserves of Fagus sylvatica and Pinus sylvestris trees influence potential enzymatic activities of their ectomycorrhizal symbionts from winter towards spring reactivation, and whether these changes influence potential soil enzymatic activities. We analyzed sugar and starch concentrations in the fine roots of Fagus sylvatica and Pinus sylvestris and potential activities of ß -glucosidase, ß -xylosidase, and cellobiohydrolase (as proxies for carbon-degrading enzymes) as well as leucine aminopeptidase and chitinase (as proxies for nitrogen-degrading enzymes) of their dominant ectomycorrhizal symbionts as well as in the soil. Sugar concentrations in the fine roots were significantly positively correlated with enzymatic activities of the ectomycorrhizal symbionts. In Pinus sylvestris , both carbon- and nitrogen-degrading enzyme activities showed significant positive correlations with fine root sugar concentrations. In Fagus sylvatica , fine root sugar concentrations were explicitly positively correlated with the activity of nitrogen-degrading enzymes. The chitinase activity in the soil was found to be strongly positively correlated with the enzymatic activity of the ectomycorrhizal symbionts as well as with fine root sugar concentrations. Fine root carbohydrate concentrations of Fagus sylvatica and Pinus sylvestris trees and enzymatic activities of their associated ectomycorrhizal fungi are connected. The specific nutrient demand of the tree species during spring reactivation may affect ectomycorrhizal enzymatic activity via carbon mobilization in the fine roots of Fagus sylvatica and Pinus sylvestris . Moreover, our results suggest that trees indirectly contribute to the degradation of fungal necromass by stimulating ectomycorrhizal chitinase activity in the soil.

Fine Root Morphology, Biochemistry and Litter Quality Indices of Fast- and Slow-growing Woody Species in Ethiopian Highland Forest - Dessie Assefa; Douglas L. Godbold; Beyene Belay; Abrham Abiyu; Boris Rewald (Ecosystems, 2018)

Soil N mineralization profiles of co-existing woody vegetation islands at the alpine tree line - Lixia Wang; Douglas L. Godbold (European Journal of Forest Research, 2017)

Response of soil microbial community to afforestation with pure and mixed species - Anna Gunina; Andrew R. Smith; Douglas L. Godbold; Davey L. Jones; Yakov Kuzyakov (Plant and Soil, 2017)

Mycorrhizas and soil ecosystem function of co-existing woody vegetation islands at the alpine tree line - Lixia Wang; Burenjargal Otgonsuren; Douglas L. Godbold (Plant and Soil, 2017)

Overyielding of temperate deciduous tree mixtures is maintained under throughfall reduction - Hans Göransson; Michael T. Bambrick; Douglas L. Godbold (Plant and Soil, 2016)

Contributions of a global network of tree diversity experiments to sustainable forest plantations - Kris Verheyen; Margot Vanhellemont; Harald Auge; Lander Baeten; Christopher Baraloto; Nadia Barsoum; Simon Bilodeau-Gauthier; Helge Bruelheide; Bastien Castagneyrol; Douglas Godbold; Josephine Haase; Andy Hector; et al. (Ambio, 2016)
The area of forest plantations is increasing worldwide helping to meet timber demand and protect natural forests. However, with global change, monospecific plantations are increasingly vulnerable to abiotic and biotic disturbances. As an adaption measure we need to move to plantations that are more diverse in genotypes, species, and structure, with a design underpinned by science. TreeDivNet, a global network of tree diversity experiments, responds to this need by assessing the advantages and disadvantages of mixed species plantations. The network currently consists of 18 experiments, distributed over 36 sites and five ecoregions. With plantations 1–15 years old, TreeDivNet can already provide relevant data for forest policy and management. In this paper, we highlight some early results on the carbon sequestration and pest resistance potential of more diverse plantations. Finally, suggestions are made for new, innovative experiments in understudied regions to complement the existing network.

Drivers of increased soil respiration in a poplar coppice exposed to elevated CO2 - Alessandra Lagomarsino; Martin Lukac; Douglas L. Godbold; Sara Marinari; Paolo De Angelis (Plant and Soil, 2013)

Tree species diversity interacts with elevated CO 2 to induce a greater root system response - Andrew R. Smith; Martin Lukac; Michael Bambrick; Franco Miglietta; Douglas L. Godbold (Global Change Biology, 2013)
As a consequence of land‐use change and the burning of fossil fuels, atmospheric concentrations of CO 2 are increasing and altering the dynamics of the carbon cycle in forest ecosystems. In a number of studies using single tree species, fine root biomass has been shown to be strongly increased by elevated CO 2 . However, natural forests are often intimate mixtures of a number of co‐occurring species. To investigate the interaction between tree mixture and elevated CO 2 , A lnus glutinosa , B etula pendula and F agus sylvatica were planted in areas of single species and a three species polyculture in a free‐air CO 2 enrichment study ( B angor FACE ). The trees were exposed to ambient or elevated CO 2 (580 μmol mol −1 ) for 4 years. Fine and coarse root biomass, together with fine root turnover and fine root morphological characteristics were measured. Fine root biomass and morphology responded differentially to the elevated CO 2 at different soil depths in the three species when grown in monocultures. In polyculture, a greater response to elevated CO 2 was observed in coarse roots to a depth of 20 cm, and fine root area index to a depth of 30 cm. Total fine root biomass was positively affected by elevated CO 2 at the end of the experiment, but not by species diversity. Our data suggest that existing biogeochemical cycling models parameterized with data from species grown in monoculture may be underestimating the belowground response to global change.

N2 fixation and cycling in Alnus glutinosa, Betula pendula and Fagus sylvatica woodland exposed to free air CO2 enrichment - Jonathan Millett; Douglas Godbold; Andrew R. Smith; Helen Grant (Oecologia, 2012)

Effect of increased atmospheric CO 2 on the performance of an aquatic detritivore through changes in water temperature and litter quality - VERÓNICA FERREIRA; ANA LÚCIA GONÇALVES; DOUGLAS L. GODBOLD; CRISTINA CANHOTO (Global Change Biology, 2010)
Cold water woodland streams, where terrestrially derived organic matter fuels aquatic food webs, can be affected by increases in atmospheric CO 2 concentrations, as these are predicted to lead to increases in water temperature and decreases in organic matter quality. In fact, elevated CO 2 (580 ppm) decreased the initial phosphorus concentration of birch litter by 30% compared with litter grown under ambient conditions (380 ppm). Here, we first assessed the effect of differences in litter quality on mass loss, microbial colonization and conditioned litter quality after submersion in a mountain stream for 2 weeks. Leaching did not change the relative differences between litter types, while fungal biomass was two fold higher in elevated litter. We then offered this litter (conditioned ambient and elevated) to a stream detritivore that was kept at 10 and 15 °C to assess the individual and interactive effects of increased temperature and decreased litter quality on invertebrate performance. When given a choice, the detritivore preferred elevated litter, but only at 10 °C. When fed litter types singularly, there was no effect of litter quality on consumption rates; however, the effect of temperature depended on individual size and time of collection. Growth rates were higher in individuals fed ambient litter at 10 °C when compared with individuals fed elevated litter at 15 °C. Mortality did not differ between litter types, but was higher at 15 °C than at 10 °C. Increases in temperature led to alterations in the individual body elemental composition and interacted with litter type. The performance of the detritivore was therefore more affected by increases in temperature than by small decreases in litter quality. However, it seems conceivable that in a future global warming scenario the simultaneous increases in water temperature and decreases in litter quality might affect detritivores performance more than predicted from the effects of both factors considered individually.

Fine root biomass and turnover in southern taiga estimated by root inclusion nets - Martin Lukac; Douglas L. Godbold (Plant and Soil, 2010)

Ectomycorrhizal community structure in a healthy and a Phytophthora-infected chestnut (Castanea sativa Mill.) stand in central Italy - Jan Maarten Blom; Andrea Vannini; Anna Maria Vettraino; Michael D. Hale; Douglas L. Godbold (Mycorrhiza, 2009)

Soil properties under Norway spruce differ in spruce dominated and mixed broadleaf forests of the Southern Taiga - Eleonora Bonifacio; Angelo Caimi; Gloria Falsone; Sergey Ya. Trofimov; Ermanno Zanini; Douglas L. Godbold (Plant and Soil, 2008)

Woody biomass production during the second rotation of a bio‐energy Populus plantation increases in a future high CO 2 world - MARION LIBERLOO; CARLO CALFAPIETRA; MARTIN LUKAC; DOUGLAS GODBOLD; ZHI‐BIN LUO; ANDREA POLLE; MARCEL R. HOOSBEEK; OLEVI KULL; MICHAL MAREK; CHRISTINE RAINES; MAURO RUBINO; GAIL TAYLOR; et al. (Global Change Biology, 2006)
The quickly rising atmospheric carbon dioxide (CO 2 )‐levels, justify the need to explore all carbon (C) sequestration possibilities that might mitigate the current CO 2 increase. Here, we report the likely impact of future increases in atmospheric CO 2 on woody biomass production of three poplar species ( Populus alba L. clone 2AS‐11, Populus nigra L. clone Jean Pourtet and Populus × euramericana clone I‐214). Trees were growing in a high‐density coppice plantation during the second rotation (i.e., regrowth after coppice; 2002–2004; POPFACE/EUROFACE). Six plots were studied, half of which were continuously fumigated with CO 2 (FACE; free air carbon dioxide enrichment of 550 ppm). Half of each plot was fertilized to study the interaction between CO 2 and nutrient fertilization. At the end of the second rotation, selective above‐ and belowground harvests were performed to estimate the productivity of this bio‐energy plantation. Fertilization did not affect growth of the poplar trees, which was likely because of the high rates of fertilization during the previous agricultural land use. In contrast, elevated CO 2 enhanced biomass production by up to 29%, and this stimulation did not differ between above‐ and belowground parts. The increased initial stump size resulting from elevated CO 2 during the first rotation (1999–2001) could not solely explain the observed final biomass increase. The larger leaf area index after canopy closure and the absence of any major photosynthetic acclimation after 6 years of fumigation caused the sustained CO 2 ‐induced biomass increase after coppice. These results suggest that, under future CO 2 concentrations, managed poplar coppice systems may exhibit higher potential for C sequestration and, thus, help mitigate climate change when used as a source of C‐neutral energy.

Mycorrhizal Hyphal Turnover as a Dominant Process for Carbon Input into Soil Organic Matter - Douglas L. Godbold; Marcel R. Hoosbeek; Martin Lukac; M. Francesca Cotrufo; Ivan A. Janssens; Reinhart Ceulemans; Andrea Polle; Eef J. Velthorst; Giuseppe Scarascia-Mugnozza; Paolo De Angelis; Franco Miglietta; Alessandro Peressotti (Plant and Soil, 2006)

Contrasting rooting patterns of some arid-zone fruit tree species from Botswana – II. Coarse root distribution - Armin L. Oppelt; Winfried Kurth; Douglas L. Godbold (Agroforestry Systems, 2005)

Contrasting rooting patterns of some arid-zone fruit tree species from Botswana – I. Fine root distribution - Armin L. Oppelt; Winfried Kurth; Georg Jentschke; Douglas L. Godbold (Agroforestry Systems, 2005)

Production, turnover and mycorrhizal colonization of root systems of three Populus species grown under elevated CO 2 (POPFACE) - MARTIN LUKAC; CARLO CALFAPIETRA; DOUGLAS L. GODBOLD (Global Change Biology, 2003)
A fast growing high density Populus plantation located in central Italy was exposed to elevated carbon dioxide for a period of three years. An elevated CO 2 treatment (550 ppm), of 200 ppm over ambient (350 ppm) was provided using a FACE technique. Standing root biomass, fine root turnover and mycorrhizal colonization of the following Populus species was examined: Populus alba L., Populus nigra L., Populus x euramericana Dode (Guinier). Elevated CO 2 increased belowground allocation of biomass in all three species examined, standing root biomass increased by 47–76% as a result of FACE treatment. Similarly, fine root biomass present in the soil increased by 35–84%. The FACE treatment resulted in 55% faster fine root turnover in P. alba and a 27% increase in turnover of roots of P. nigra and P. x euramericana . P. alba and P. nigr a invested more root biomass into deeper soil horizon under elevated CO 2 . Response of the mycorrhizal community to elevated CO 2 was more varied, the rate of infection increased only in P. alba for both ectomycorrhizal (EM) and arbuscular mycorrhizas (AM). The roots of P. nigra showed greater infection only by AM and the colonization of the root system of P. x euramericana was not affected by FACE treatment. The results suggest that elevated atmospheric CO 2 conditions induce greater belowground biomass investment, which could lead to accumulation of assimilated C in the soil profile. This may have implications for C sequestration and must be taken into account when considering long‐term C storage in the soil.

Does soil acidity reduce subsoil rooting in Norway spruce (Picea abies)? - Georg Jentschke; Michael Drexhage; Heinz-Werner Fritz; Eberhard Fritz; Bruno Schella; Do-Hyung Lee; Franz Gruber; Jutta Heimann; Maike Kuhr; Joachim Schmidt; Susanne Schmidt; Reiner Zimmermann; et al. (Plant and Soil, 2001)

Nitrogen limitation in mycorrhizal Norway spruce (Picea abies) seedlings induced mycelial foraging for ammonium: implications for Ca and Mg uptake - Georg Jentschke; Douglas L. Godbold; Bettina Brandes (Plant and Soil, 2001)

The mycorrhizal fungus Paxillus involutus transports magnesium to Norway spruce seedlings. Evidence from stable isotope labeling - Georg Jentschke; Bettina Brandes; Arnd J. Kuhn; Walter H. Schröder; J. Sabine Becker; Douglas L. Godbold (Plant and Soil, 2000)

Cation exchange capacity and lead sorption in ectomycorrhizal fungi - Petra Marschner; Georg Jentschke; Douglas L. Godbold (Plant and Soil, 1998)